2021
DOI: 10.1126/sciadv.abg0677
|View full text |Cite
|
Sign up to set email alerts
|

Animal welfare risks of global aquaculture

Abstract: The unprecedented growth of aquaculture involves well-documented environmental and public-health costs, but less is understood about global animal welfare risks. Integrating data from multiple sources, we estimated the taxonomic diversity of farmed aquatic animals, the number of individuals killed annually, and the species-specific welfare knowledge (absence of which indicates extreme risk). In 2018, FAO reported 82.12 million metric tons of farmed aquatic animals from six phyla and at least 408 species—20 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 77 publications
(91 reference statements)
0
49
0
Order By: Relevance
“…Using all such development avenues, QBA descriptor lists and dimensions can be further validated and tested for efficacy. Given the growth of aquaculture globally and the large number of species and individual fish involved ( 4 ), there is a need to develop reliable tools for monitoring fish welfare (including positive welfare), that can inform guidance and legislation to meet the species-specific needs of fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using all such development avenues, QBA descriptor lists and dimensions can be further validated and tested for efficacy. Given the growth of aquaculture globally and the large number of species and individual fish involved ( 4 ), there is a need to develop reliable tools for monitoring fish welfare (including positive welfare), that can inform guidance and legislation to meet the species-specific needs of fish.…”
Section: Discussionmentioning
confidence: 99%
“…These systems will impact fish welfare in different ways, exposing them to different stress challenges and hazards, and presenting the risk that the animals' environmental and behavioral needs, both at individual and group level, are not met ( 3 ). Given the rapid increase in aquaculture production and the range of species now farmed, there is thus an urgent need to address the welfare of farmed fish, and, as with other farmed animal species, to develop methods that monitor the different species' needs ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research underscoring sentience and the ability to feel pain within marine species targeted by seafood producers has led, among other things, to recent calls to ban octopus aquaculture and electric pulse fishing (Browman et al, 2019;Jacquet et al, 2019). At the same time, while aquaculture has rapidly expanded to include at least 408 species (FAO, 2020), specialized welfare information is only available for 84 of these (Franks et al, 2021), pointing to a vast gray area at the core of seafood production. Yet perceptions of animal welfare are not universal, and represent a dynamic and evolving aspect of what constitutes sustainable and ethical seafood.…”
Section: Social Norms Of Animal Welfare and Consumptionmentioning
confidence: 99%
“…Fisheries have already reached their limits [9] and the increase in fish consumption over the past four decades is mainly covered by aquaculture, which is the world's fastestgrowing food production industry [10]. This growth involves environmental problems and animal welfare risks [11]. In 2000, a study concluded that aquaculture needs to reduce wild fish inputs into feed [12].…”
Section: Introductionmentioning
confidence: 99%